Dental Smart Book Media to Dental Health Knowledge in Junior High School - Safitri, Nida Maharani; Emini, Emini; Fajderi, Indrayati; Ngatemi, Ngatemi (Center of Excellent (Pusat Unggulan Iptek), 2026)
Background: Based on data from the Indonesian Health Survey (SKI, 2023), there is a 56.9% proportion of dental health problems in Indonesia. Therefore, strategies are needed to address these issues, one of which is through promotive efforts. Effective counselling is influenced by the media and methods used, such as utilizing the dental smart book, which is a development of dental health education media. Objective: To obtain an overview of dental health knowledge before and after counselling using the dental smart book media among students of Junior High School Muhammadiyah 29 Sawangan Depok. Method: This research was conducted using a quasi-experimental method with a pre-test and post-test design. The study was carried out at SMP Muhammadiyah 29 Sawangan Depok. The sampling technique used was total sampling, with a total of 32 students as respondents. The instruments used were questionnaires and the dental smart book media. Results: The study showed that 30 students (93.8%) were in the good category and 2 students (6.2%) were in the sufficient category after being given the intervention using the dental smart book media. Conclusion: The dental smart book media is effective in improving dental health knowledge among eighth-grade students of of Junior High School Muhammadiyah 29 Sawangan Depok